Cellular senescence as a response to multiwalled carbon nanotube (MWCNT) exposure in human mesothelial cells. (January 2021) - Reamon-Buettner, Stella Marie; Hackbarth, Anja; Leonhardt, Albrecht; Braun, Armin; Ziemann, Christina
Highlights: Certain multiwalled carbon nanotubes can induce cellular senescence. Primary human mesothelial cells display SAHFs, SADSs, and LMNB1 depletion. There is widespread impairment of the cytoskeleton and the chromatin. Transcriptome analyses show signature for senescence-associated secretory phenotype. Abstract: Cellular senescence is a stable cell cycle arrest induced by diverse triggers, including replicative exhaustion, DNA damaging agents, oncogene activation, oxidative stress, and chromatin disruption. With important roles in aging and tumor suppression, cellular senescence has been implicated also in tumor promotion. Here we show that certain multiwalled carbon nanotubes (MWCNTs), as fiber-like nanomaterials, can trigger cellular senescence in primary human mesothelial cells. Using in vitro approaches, we found manifestation of several markers of cellular senescence, especially after exposure to a long and straight MWCNT. These included inhibition of cell division, senescence-associated heterochromatin foci, senescence-associated distension of satellites, LMNB1 depletion, γH2A.X nuclear panstaining, and enlarged cells exhibiting senescence-associated β-galactosidase activity. Furthermore, genome-wide transcriptome analysis revealed many differentially expressed genes, among which were genes encoding for a senescence-associated secretory phenotype. Our results clearly demonstrate the potential of long and straight MWCNTs to induce premature cellular senescence. This finding may find relevance in risk assessment of workplace safety, and in evaluating MWCNT's use in medicine such as drug carrier, due to exposure effects that might prompt onset of age-related diseases, or even carcinogenesis.